One Health – Important Component of the Global Health Security (One Health & Risk Management, 2021)
One Health is a new interdisciplinary trend that has to be addressed when national and international plans and strategies related to zoonotic diseases, food safety, antimicrobial resistance, and climate change are established.
Keywords: One Health; Global Health Security